Fast-FISH technique for rapid, simultaneous labeling of all human centromeres - Durm, Markus; Sorokine-Durm, Irène; Haar, Frank-Martin; Hausmann, Michael; Ludwig, Horst; Voisin, Philippe; Cremer, Christoph (Cytometry, 1998)
Fluorescence in situ hybridization (FISH) has become a powerful tool in chromosome analysis. This report describes the systematic optimization of the Fast-FISH technique for centromere labeling of human metaphase chromosomes for radiobiological dosimetry purposes. For the present study, the hybridization conditions and the efficiency of two commercially available α-satellite DNA probes were compared (“human chromosome 1 specific”, Oncor, Gaithersburg, MD, vs. “all-human chromosomes specific”, Boehringer-Mannheim, Germany). These probes were hybridized to human lymphocyte metaphase plates by using a hybridization buffer without formamide and without any other equivalent denaturing chemical agents. The results indicate the suitability of the method for automated image analysis on the basis of thresholding. The optimal conditions concerning hybridization time and temperature were determined by a systematic quantitative evaluation of the fluorescent labeling sites after the hybridization procedures. Under defined “low stringency” conditions, we found that the “human chromosome 1 specific” DNA probe labeled not only the centromere of the human chromosome 1 but also the other human centromeres in the same way as the “all-human chromosome specific” DNA probe. The optimized conditions to complete all centromere labeling were applied to the detection of dicentric chromosomes on irradiated human lymphocyte samples (γ-rays of 60Co source, 0.5 Gy/min, for doses of 1, 3, and 4 Gy). The yield of dicentrics was determined after Fast-FISH and compared with results obtained after Giemsa staining. These results are very compatible and indicate that, because of its simplicity, this optimized Fast-FISH procedure would be useful for fast screening purposes in biological dosimetry after accidental overexposure. Cytometry 31:153-162, 1998. © 1998 Wiley-Liss, Inc.
Gesehen am 03.07.2023